(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The article discusses the theoretical and methodological foundations of modern pragmalinguistics. The process of pragmalinguistics entering the field of linguistics, its development and the different views of scientists is described.